Dynamics of Gut Microbiota Diversity During the Early Development of an Avian Host: Evidence From a Cross-Foster Experiment - Teyssier, Aimeric; Lens, Luc; Matthysen, Erik; White, Joël (Frontiers in Microbiology, 2018)
Despite the increasing knowledge on the processes involved in the acquisition and development of the gut microbiota in model organisms, the factors influencing early microbiota successions in natural populations remain poorly understood. In particular, little is known on the role of the rearing environment in the establishment of the gut microbiota in wild birds. Here, we examined the influence of the nesting environment on the gut microbiota of Great tits (Parus major) by performing a partial cross-fostering experiment during the intermediate stage of nestling development. We found that the cloacal microbiota of great tit nestlings underwent substantial changes between 8 and 15 days of age, with a strong decrease in diversity, an increase in the relative abundance of Firmicutes and a shift in the functional features of the community. Second, the nesting environment significantly influenced community composition, with a divergence among separated true siblings and a convergence among foster siblings. Third, larger shifts in both microbiota diversity and composition correlated with lower nestling body condition. Our results shed new light on the dynamics of microbial diversity during the ontogeny of avian hosts, indicating that the nest environment continues to shape the gut microbiota during the later stages of nestling development and that the increase in gut diversity between hatching and adulthood may not be as linear as previously suspected. Lastly, the microbiota changes incurred during this period may have implications for nestling body condition which can lead to long-term consequences for host fitness.